Condições sensíveis à atenção primária como dispositivo de gestão do cuidado em saúde: a apropriação pelos usuários do SUS - Malvezzi, Edson (Universidade Federal de São Carlos, 2019)
Despite advances in the last thirty years, the Brazilian public health system still faces impasses for its consolidation as a social policy to foster citizenship and the challenge of breaking with the traditional care model in the daily services. With the perspective of structuring new forms of care management, organization of supply and guarantee of continuity, the "ICSAP Project - hospitalizations for conditions sensitive to primary care" in the city of Campinas-SP was designed and implemented in 2012, which seeks to articulate and negotiate actions between the services of a specific territory, especially the basic health units and the hospital, in order to qualify and guarantee the access and continuity of the care of its users. Taking this initiative as an object, this research aims to analyze the perceptions of these users regarding their appropriation of public health policy, in particular the understanding, repercussions and participation in the processes of organization, operationalization and evaluation of the health system and services in which they are inserted. This is a qualitative study with a documentary survey and data collection through interviews with users, the results being systematized according to content analysis and discussed in the light of critical hermeneutics and the "Paidéia" reference. The findings demonstrate that users recognize the Unified Health System as a public policy, aiming to know their logic of operation and the benefits offered by their services when they need health care; in an analogous way, recognize and perceive the effects of the "ICSAP Project", especially for the institution of new practices in the care after hospital hospitalization episode in the basic units; however, it is evidenced that these users were not included in the institutional spaces of social participation for discussion, organization and evaluation of this initiative, as well as the health system in general, demonstrating that there are still challenges to their effective appropriations by society. From this scenario, it is hoped to contribute to the reflection in the different instances of this system, especially in Campinas, and in society in general, about the necessary expansion of the inclusion of users in the deliberative processes of both the "ICSAP Project" and in the organization of the health system.
Conditions sensitive to primary care as a health care management device: the appropriation by SUS users
Keywords: Ciência, tecnologia e sociedade; Gestão de ciência, tecnologia e inovação em saúde; Política pública; Controle social formal; Science, technology and society; Health sciences, technology and innovation management; Public policy; Social control formal; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE DO PROCESSO DECISORIO